The Relationship Between Experienced Parents’ Divorce and Their Circumstancs With Young Adults’ Behavioral and Emotional Difficulties - Viršilaitė, Reda; Bukšnytė-Marmienė, Loreta (Pedagogika, 2023)
Parents’ divorce is a phenomenon affecting the further psychosocial functioning of children. It is established that the divorce consequences on children are long-term: adults who have experienced parents’ divorce in childhood are characterized by poorer mental health, also they are having clearer emotional and behavioral difficulties. Researchers argue that not the divorce fact itself is the most important in assessing the consequences for children but rather the circumstances of parents’ divorce. After analysing the most detrimental divorces’ circumstances this study focuses on the child’s negative feelings, experienced during the divorce, the intensity of parents’ conflicts, the child’s involvement in conflicts, and negative changes afterwards. The aim of the study was to determine the relationship between young adults’ behavioral and emotional difficulties and parents’ divorce experienced in childhood or adolescence as well as its circumstances. The study involved 173 young adults. Behavioral and emotional difficulties are assessed by ASEBA (Adult Questionnaire). In order to assess the impact of parents’ divorce and its circumstances, a questionnaire (Viršilaitė, Bukšnytė-Marmienė, 2018) was used. The study found that the child’s negative feelings during parents’ divorce predict young adults’ aggression, rules’ braking, anxiety/depression, self-closure also emotional and behavioral difficulties in general. The intensity of parents’ conflicts during divorce predicts aggression in young adults.